The perceiving and creating on process of visual representation of fashion design (ModaPalavra e-periódico, 2008)
The objective of this research is the study of things that guide the process of visual representation - by the artistic design - with its aesthetic functions, illustrative and functional, and its application at the conceptual phases of project design of products of fashion.
Keywords: Visual representation; artistic design; design of products